Initial thoughts on comparing computational design creativity systems. Issue 1 (3rd April 2019) - Brown, David C.
Abstract: This paper describes an initial investigation into models that might be useful to describe and compare computational design creativity (CDC) systems. An existing approach to creative system comparison, the FACE model, is critiqued, and discovered to be a weak match with design systems. Informed by this discovery, an alternative more design-oriented, ontology-based approach is proposed that describes systems in terms of design-oriented processes. Various proposals in the literature about design reasoning processes are evaluated for inclusion in an ontology of processes that could be used for CDC comparison, using criteria that are developed and presented in this paper.